Greater than the sum of its parts: optical remote sensing and sediment core data provide a holistic perspective on glacial processes - Henry Jacob Miller Gage; Carolyn Hope Eyles (Journal of Glaciology)
In this letter we make the case that closer integration of sediment core and passive optical remote sensing data would provide new insights into past and contemporary glacio-sedimentary processes. Sediment cores are frequently used to study past glacial processes and environments as they contain a lengthy geochemical and sedimentological record of changing conditions. In contrast, optical remote sensing imagery is used extensively to examine contemporary glacial processes, including meltwater dynamics, glacial retreat, calving, and ice accumulation. While paleoenvironmental data from sediment cores and optical remote sensing imagery are rarely used in tandem, they are complementary. Sediment core records are spatially discrete, providing long-term paleoenvironmental proxy data which require assumptions about environment-sediment linkages. Optical imagery offers precise, spatially extensive data to visualize contemporary processes often limited in their temporal extent. We suggest that methodologies which integrate optical remotely sensing with sediment core data allow direct observation of processes interpolated from sedimentological analysis and achieve a more holistic perspective on glacial processes. This integration addresses the limitations of both data sources and can achieve a stronger understanding of glacier dynamics by expanding the spatiotemporal extent of data, reducing the uncertainty of interpretations, and broadening the local analyses to regional and global scales.